Susceptibility of a Simple Transmission Line Inside an Enclosure Against Normal Incident Plane Wave - Abadpour , S.; Dehkhoda , P.; Moini , R.; Sadeghi , S. H. H.; Karami , H. R. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, susceptibility of a Microstrip Transmission Line (MTL) as a simple Printed Circuit Board (PCB) against a normal incident plane wave is studied. Here, the induced voltage on the open port of the MTL is considered as the susceptibility criterion for the MTL. Two different approaches are applied: the Method of Moments (MoM) and the Finite Integration Technique (FIT). In addition to simulations, we performed measurements inside a semi-anechoic chamber. Both simulations show very good agreement with the measurements. In addition to frequency domain results, time domain induced open circuit voltage is calculated. The effect of different aperture sizes on the susceptibility of a shielded MTL is examined. It is shown that large apertures can multiply the disagreeable effect of the interfering wave on the MTL, compared to the case where no shield is utilized.